2020
DOI: 10.24326/asphc.2020.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Yield and Quality of 'Florida King' Peaches Subjected to Foliar Calcium Chloride Sprays at Different Growth Stages

Abstract: Peach fruit and trees are prone to various issues, regarding yield, quality and pest attack. Calcium plays several roles in plant and fruit development. Therefore the current study was conducted to evaluate the response of peach fruit to foliar application. The experiment was laid out in Randomized Complete Block Design with two factors factorial arrangement and three replicates. Calcium chloride was applied at the rate of 0, 1, 2 and 3%. The foliar application of calcium was done at pink bud stage, berry size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The improvement of fruit physical properties indicated in this study could be attributed to their roles in alleviating stress impacts, preserving osmotic balance, protecting the photosynthetic products, scavenging free radicals and improving fruit development during growth stages (Galston et al, 1997, Ismail et al, 2014, Ali, 2014and Trovato et al, 2019. Shahid et al (2020) showed that preharvest application of calcium chloride during fruit growth stages increased fruit weight, diameter and flesh weight. Furthermore, preharvest application of salicylic acid enhanced physical characteristics of Egypt.…”
Section: Discussionmentioning
confidence: 59%
“…The improvement of fruit physical properties indicated in this study could be attributed to their roles in alleviating stress impacts, preserving osmotic balance, protecting the photosynthetic products, scavenging free radicals and improving fruit development during growth stages (Galston et al, 1997, Ismail et al, 2014, Ali, 2014and Trovato et al, 2019. Shahid et al (2020) showed that preharvest application of calcium chloride during fruit growth stages increased fruit weight, diameter and flesh weight. Furthermore, preharvest application of salicylic acid enhanced physical characteristics of Egypt.…”
Section: Discussionmentioning
confidence: 59%
“…The results of this study show that berry firmness increases after CaNO3 application. Many other studies have reported a significant relationship between calcium levels and fruit firmness in apples, blueberries, and peaches (Mohebbi et al, 2020;Shahid et al, 2020;Lobos et al, 2021). According to a recent study in grapes (Martins et al, 2020), the internal structure of the berry changes due to the expression of genes that prevent pectin degradation and cell wall softening, thus leading to berry firmness.…”
Section: Resultsmentioning
confidence: 99%